Unity Medical Visualization: 01 Preparation and Design. - Thorn, Alan (linkedin.com, 2020)
Learn how to use Unity to build an interactive 3D visualization of the human heart. Part 01 covers asset import, scene and level design, interactivity, and post-processing effects.